2015
DOI: 10.1302/0301-620x.97b1.34038
|View full text |Cite
|
Sign up to set email alerts
|

Capsule repair may reduce dislocation following hip hemiarthroplasty through a direct lateral approach

Abstract: Reported rates of dislocation in hip hemiarthroplasty (HA) for the treatment of intra-capsular fractures of the hip, range between 1% and 10%. HA is frequently performed through a direct lateral surgical approach. The aim of this study is to determine the contribution of the anterior capsule to the stability of a cemented HA through a direct lateral approach. A total of five whole-body cadavers were thawed at room temperature, providing ten hip joints for investigation. A Thompson HA was cemented in place via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…We believe that, in general, not enough attention is paid to the breaking and removal of certain structures in hip replacement surgery and also in post‐operative rehabilitation. For example, the decision to perform a capsulectomy may be based on the surgeon's personal choice according to experience, on the surgical path (which is essential in the postero‐lateral pathway) and the need for wider exposure 26‐29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that, in general, not enough attention is paid to the breaking and removal of certain structures in hip replacement surgery and also in post‐operative rehabilitation. For example, the decision to perform a capsulectomy may be based on the surgeon's personal choice according to experience, on the surgical path (which is essential in the postero‐lateral pathway) and the need for wider exposure 26‐29 …”
Section: Discussionmentioning
confidence: 99%
“…The tendon must be preserved without any damage, due to its essential mechanical functions, 40 but low innervation may demonstrate the lesser role of this structure as pain generator. As regards the capsule, Hughes et al 29 suggest maintaining the capsular structure as well, improving proprioception and relieving pain, especially during the first postsurgery weeks. However, our results confirm that capsulectomy in hip replacement surgery does not particularly influence patients' pain, matching the results of Gáspár et al 10 who evaluated 22 joint capsules excised after arthroplasty surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have examined the stability augmented by capsular repair of THA performed through the DAA, however, Hughes et al examined the effect of capsular repair in cadavers following hip hemiarthroplasty through a direct lateral approach and found that capsular repair required a 4-fold higher peak torque force to dislocate anteriorly [22]. Infection reduction in capsular repair has also not been directly evaluated, however, preserving additional anatomic layers might assist in microbial blockade.…”
Section: Resultsmentioning
confidence: 99%
“…8 It has been previously shown that capsular repair may reduce the risk of dislocations after hemiarthroplasty and total hip arthroplasty. 12,13 Several other studies also have shown that the hip capsule influences biomechanical and clinical stability in patients after total hip arthroplasty. [14][15][16][17] Cooper et al 18 found that the thickest parts of the capsule in the acetabular origin are posterosuperior and superolateral and anterior at the femoral insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Capsular Reconstruction (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) 7. Preparing the capsular surface comprises 2 procedures: debridement of the scar tissue where the capsule once was and decortication of the acetabular and femoral beds for a better graft incorporation.…”
Section: Diagnostic Arthroscopy and Treatment To Address Pathology (5-6)mentioning
confidence: 99%